AUTO - TEST OF BREASTS: PRACTICE OF NURSING PROFESSIONALS OF FAMILY HEALTH STRATEGY (Fiep Bulletin - online, 2016)
The screen study aims to describe the factors that hamper achievement of a self-breast examination by professionals. This is a descriptive study with quantitative approach developed in the city of Cajazeiras with nursing professionals who make up the Family Health Strategy. The sample consisted of 26 professionals who make up the nursing staff. Data collection was carried out in May 2013, through the application of a form in accordance with the objectives proposed in the study. The collected data were organized in an electronic database of the Microsoft Excel application being coded, tabulated and presented in tables, charts and graphs with their respective percentage distributions. Of the surveyed professionals predominated the number of women who use oral contraceptives. The nursing professionals, mostly claimed to have relatives with breast cancer. Among the preventive actions taken by nursing techniques, the most mentioned were: consultation with the doctor, self-examination and ultrasonography. As for the nurses were: the ultrasound and self-breast examination. The reasons given for not performing self-examination by the professionals were: forgetfulness, lack of interest and lack of time. In the present study it was observed that the professionals performed the self-breast examination, however it needs that they can adhere to this practice in order to provide security and provide a good physical, social and emotional.
Keywords: self-examination; Nursing; Prevention.